Pengaruh Sistem Pembayaran Digital Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Orange Carwash - Rizka Amelia; Dianing Widya Kusumastuti (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to examine the influence of digital payment systems and service quality on customer satisfaction at Orange Carwash Kartasura. The background of this research arises from the growing trend of digital technology adoption in the era of the cashless society, which encourages service companies to adapt, particularly in payment systems and customer service. The study employed a quantitative method by distributing questionnaires to 103 Orange Carwash customers. Data were analyzed using SPSS version 25 to test validity, reliability, classical assumptions, multiple linear regression, t-test, F-test, and the coefficient of determination. The results indicate that both digital payment systems and service quality have a positive and significant effect on customer satisfaction, either partially or simultaneously. These findings demonstrate that the better the implementation of digital payment systems and the higher the service quality provided, the greater the level of customer satisfaction. This research is expected to serve as a reference for developing service strategies and implementing digital technology in the service sector.